Novel Liberalism Coefficient to Improve Human Freedom Development in the World (LACCEI, 2024)
Abstract— The new concept to measure human freedom examines the relationship of the Coefficient of Liberalism (L) and, the variables grouped in three dimensions: the forces of modern markets, private property and, Institutionality. The analyzed population corresponded to 116 countries. 158 variables were collected per country for 10 years. For the analysis, information from The Global Competitiveness Index Historical Dataset © 2008-2018 of the World Economic Forum was used, with which an Xnxl Database was used with index and coefficient values, country codes, global id, identified series and treatments (Income groups, Regions and Forum classification). The hypothesis test, linear regression analysis, ANOVA, PCA, univariate variance and eta-square were used as statistics. The L Coefficient has a statistically significant positive correlation with the Global Competitiveness Index (R2=0,82 F(1,114) = 516,61 Sig.=,000)) and, it served to evaluate the three treatments analyzed. The means of the income groups differ significantly, F(1,112) = 5,68, p ,001, η2 = 0,14 for the dependent variable of the Coefficient of Liberalism (L). In addition, the means of the Regions differ significantly, F(1,109) = 2,77, p 001, η2 = 0,14. The squared Eta value indicated a large effect of income groups and Regions on the L Coefficient. The five countries with the highest L Coefficient were United States (14,56), Hong Kong SAR (12,63), Singapore (12,60), Canada (12,28) and Germany (12,23). This analysis confirmed the power of the L Coefficient to identify the countries that maximize human freedom.